Dinamika Pengaturan Wakaf Dalam Perspektif Hukum Perdata Islam di Indonesia - Trevio Firman Alif; Sysy Nur Sabina; Utiya Sahla Kamila; Nazwa Puspa Miranda; M. Asari El Sa'bani; Rosdiana Rosdiana (J-Alif : Jurnal Penelitian Hukum Ekonomi Syariah dan Budaya Islam, 2026)
This study analyzes the dynamics of waqf regulation within the framework of Islamic civil law in Indonesia by examining its legal transformation and practical challenges. The research focuses on the legal foundation, validity requirements, governance of waqf assets, regulation of asset alteration, and dispute resolution mechanisms. Using a normative juridical method with statutory and conceptual approaches, this study refers to UU No. 41 of 2004 on Waqf and relevant literature. The findings reveal a paradigm shift from traditional religious practice to a formal legal regime integrated into the national legal system with socio-economic orientation. However, the regulatory framework remains fragmented and faces challenges such as weak institutional governance, administrative inconsistencies, and recurring disputes. The conditional flexibility in altering waqf assets reflects a tension between classical doctrine and modern legal needs. This study concludes that regulatory harmonization and institutional strengthening are essential to optimize waqf’s role in Indonesia.